Ulfila's Own Conversion - Sivan, Hagith (Harvard theological review, 1996)
Ulfila the Goth (ca. 310–383) has gained fame as the Arian apostle to his people. More accurately, he was responsible for the conversion of semi-Arianism during the 340s. Yet two distinct traditions exist regarding Ulfila's own religious formation. One is an Arianized version of his life in the reports of Philostorgius and Auxentius, which claims Ulfila as an Arian from birth. The other, a Nicene version gleaned from the works of Socrates, Sozomen, and Theodoret, asserts that Ulfila “converted” from Nicene orthodoxy to Arianism sometime between 360 and 376. How compelling is either biography? If, moreover, Ulfila had remained loyal to Nicene doctrines until at least 360, to what had he converted the Goths in the 340s?